â€œANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION EFFECTIVENESS BASED ON GLOBAL REPORT INITIATIVE GUIDELIBNESâ€ - Sari, Yulia Manda; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2013)
The primary objective of this research is to find out how far is the application ofÂ  Corporate Social Responsibility and the level of fulfillmentÂ  applied by PT.Kaltim Prima Coal, Tbk.Â  related to continuous reports in 2010 which was based on indicators of GRI. Indicators that will be discussed comprise economic, environmental, labour, proper work, human right and product responsibility indicators. The researcher made theÂ  analysis based on those indicators and divided into 3 criteria ofÂ  fulfillment including unfulfilled, partially unfulfilled and fully fulfilled. In this research, the method used was a descriptive qualitatitive with a case study approach. The result of the analysisÂ  shows that the sustainable report ofÂ Â Â Â  PT Kaltim prima coal,tbk, overally fulfills a 82% main indicator and a-97%-additional indicator while a-10% partially unfulfilled main indicator and a-3%-additional indicator. Therefore, PT. Kaltim Prima Coal, Inc. Is categorized into â€œB+â€ as it already fulfilled more than 20 indicators whichÂ  is a minimum standard determined by GRI. Keyword: CSR, Sustainability Report, PT Kaltim Prima Coal, GRI